A dual-crosslinked self-healing and antibacterial nanocellulose hydrogel for monitoring of human motions. (March 2022) - Zhang, Luyu; Wan, Caichao; Su, Jiahui; Zhang, Chonghao; Wei, Song; Tian, Wenyan; Liu, Xinyi; Cheng, Wenjie; Li, Xingong; Li, Xianjun; Guo, Xin; Yong, Ken-Tye; et al.
Graphical abstract: Highlights: The dual-crosslinked nanocellulose-borax-PVA hydrogel is constructed. The excellent shape controllability, flexibility, and transmittance are realized. The hydrogel achieves a high healing efficiency after 300 s of self-healing. The hydrogel can act as a green platform for strain sensors and antibacterial agents. Abstract: High stiffness of hydrogen-bond network generally endows cellulose hydrogels with weak mechanical flexibility and shape uncontrollability, imposing restrictions on their application scopes. Herein, a flexible polyvinyl alcohol (PVA) network is penetrated through the rigid network of bamboo cellulose, inducing the formation of a dual-crosslinked hydrogel with superior flexibility and shape controllability. Besides, the borax crosslinker offers the bamboo nanocellulose-borax-PVA hydrogel with remarkable self-healing ability and high ionic conductivity. The hydrogel achieves a minimum sensing weight of 5 g (gauge factor: 1.47) and has a stable sensing sensitivity in both hot and cold environments (i.e., 0 and 60 °C). When fixed to the wrist of human, the hydrogel can regularly sense the motion signals, verifying the potential of the hydrogel for the development of next-generation wearable products. More importantly, the hydrogel can serve as a green platform to integrate with amoxicillin to create an effective composite to inhibit the growth of Escherichia coli and Staphylococcus aureus, which provides an effective route to develop eco-friendly and powerful functional composites. The drug-loaded hydrogel displays a negligible cytotoxicity and favorable biocompatibility towards human skin.